Curial e Güelfa i Boccaccio: influències lingüístiques. - RIGUAL, CESÁREO CALVO (Scripta, 2013)
Several scholars have found in Curial e Güelfa very clear traces of influence of Italian literature, and in particular of Boccaccio. Therefore, no other Italian influence, the purely linguistic one, has not been studied. A detailed study of the Curial has identified many elements that show their italian origin. Many of these elements are present in the works of Boccaccio, specifically in the Decameron. For each item identified in Curial, we provide some examples from the works of Boccaccio.